The deep - Dunmore, Helen, 1952- (London : HarperCollins Publishers, 2012)
Sapphire can swim in the ocean alongside her Mer friends and walk on the rocky shores of the Cornwall coast because of her mixed blood, but when the Kracken stirs in the deep, only Sapphire can swim far enough away from the light to confront the monster and save both of her homes.
5.0
5-8.
5-8
Keywords: Kraken -- Juvenile fiction; Mermaids -- Juvenile fiction; Mermen -- Juvenile fiction; Kraken -- Fiction; Mermaids -- Fiction; Mermen -- Fiction; Mermaids and mermen -- Fiction; Monsters -- Fiction; Cornwall (England : County) -- Juvenile fiction; England -- Juvenile fiction; Cornwall (England : County) -- Fiction; England -- Fiction; Cornwall (England : County) -- Fiction; England -- Fiction